The Phenomena of The Cryptocurrency Fall in The Sharia Economic View - Setya Negara, Ade Irma (HM Publisher, 2024)
Digital money was first developed in the 1960s when Western Union introduced electronic funds transfers (EFT). In Indonesia, digital money only became popular around 2007. Electronic money regulations are contained in Bank Indonesia Regulation Number 11/12/PBI/2009. Cryptocurrencies are made from a combination of blockchain technology and cryptography. Blockchain is a technology for recording interconnected transactions using unique and immutable codes. On the other hand, Cryptography is a branch of computer science that studies how to hide information. This research aims to obtain answers regarding cryptocurrencies as currency/method of exchange/assets/commodities in Indonesia. The theory applied is the theory of legal and vanity business transactions in Islam. This research is a literature study and is qualitative in nature. The data analysis technique used is analytical descriptive with a normative juridical Islamic law approach. From this research, the results show that cryptocurrencies are haram, referring to the MUI Fatwa, the decisions of the Laznah Bahtsul Masail East Java Nahdathul Ulama Regional Management (PWNU), the Tarjih Council and the Tajdin Central Executive of Muhammadiyah, the opinion of Islamic economics academics. The factors that make cryptocurrencies illegal because they are considered to contain speculation, maysir and are vulnerable to being used for illegal activities. The weaknesses of cryptocurrency are marked by the fall of crypto throughout 2022 and are predicted to continue in 2023. Crypto is illegal lighairihi or haram due to external factors, so it should be avoided.